Corporate governance........... - Das, Subhash Chandra (New Delhi: Prentice-Hall of India Pvt.Ltd, 2009)
The systems and practices of corporate governance vary from one country to another. This textbook gives a conceptual and evaluative study of the principles, codes, practices and of corporate governance prevalent in the developed as well as developing nations of the world. It discusses in detail the corporate governance codes and recommendations of national and international committees. The book is incorporated with sample study analysis of six Indian industries comprising globally renowned companies. Intended for the students of commerce, law and management, the book can be beneficial for the researchers, professionals and regulatory authorities.